Intergroup attitudes of black learners attending a multiracial school and black learners attending a single race school - Moholola, Faith Mapula (My University, 2008)
ABSTRACT Desegregated schools have provided many learners of different racial and ethnic groups the opportunity to encounter regular intergroup contact. However for those learners who attend racially segregated schools the opportunity for regular intergroup contact is limited. According to the contact hypothesis frequent integroup contact between members of different social groups can promote positive intergroup attitudes, providing that contact occurs under favourable conditions. This research compares the intergroup attitudes of Black learners attending a multiracial school (desegregated school) and Black learners attending a single race school (segregated school). A sample of 106 Black learners completed questionnaires, consisting of a number of sub-scales derived from two surveys of Holtman (2002) and Muianga (2005). The questionnaires assessed factors relating to the level of affective prejudice, social distance, the amount of general contact with Whites outside the school context, the degree of racial identification, meta-stereotype, social distance, school contact with White learners and experience of contact with White learners. For the purpose of the current study only responses from Black learners were required. Two statistical analyses were used to analyse the data: t-test analysis and multiple linear regression analysis. The t-test analysis revealed significant results indicating that Black learners attending the multiracial school encounter more general contact with Whites outside of the school context and have lower levels of social distance than Black learners in the single race school. Results of the multiple linear regression analysis for Black learners in each school revealed that meta-stereotype is the strongest factor that explains affective prejudice amongst Black learners in each school. Similarly results of the multiple linear regression analysis using the whole sample revealed that metastereotype is a significant predictor of affective prejudice, substantiating results reported by the two separate multiple linear regression analysis of affective prejudice. Results of multiple linear regression analysis concerning social distance reveal that none of the entered variables explained social distance amongst Black learners in the single race school. However experience of contact with White learners emerged as the only factor that explains social distance amongst Black learners attending the multiracial school. In addition the multiple linear regression analysis of the whole sample revealed that the type of school that the learners attend contributes significantly to social distance of the Black learners. The result of the study support the contact hypothesis in that it reveals that Black learners with greater amounts of contact with Whites have more positive feelings towards interactions with Whites. The study argues that intergroup attitudes of Black learners in both the multiracial and single race school is primarily shaped by social changes that have occurred since 1994 and social norms that govern the nature of interracial contact amongst South Africans. These factors together with underlying internal factors outlined in the study mediate intergroup attitudes of Black learners used in this study.